Prediction of the progression of joint space narrowing in osteoarthritis of the knee by bone scintigraphy. Issue 8 (August 1993) - Dieppe, P; Cushnaghan, J; Young, P; Kirwan, J
Abstract : OBJECTIVES--To test the hypothesis that bone scintigraphy will predict the outcome of osteoarthritis (OA) of the knee joint. METHODS--Ninety four patients (65 women, 29 men; mean age 64.2 years) with established OA of one or both knee joints were examined in 1986, when radiographs and bone scan images (early and late phase) were also obtained. The patients were recalled, re-examined, and had further radiographs taken in 1991. Paired entry and outcome radiographs were read by a single observer, blinded to date order and other data. Scan findings and other entry variables were related to outcome. Progression of OA of the knee was defined as an operation on the knee or a decrease in the tibiofemoral joint space of 2 mm or more. RESULTS--Over the five year study period 10 patients died and nine were lost to follow up. Fifteen had an operation on one or both knees (22 knees). Of the remaining 120 knees (60 patients) analysed radiographically, 14 (12%) had progressed in the manner defined. Of 32 knees with severe scan abnormalities, 28 (88%) showed progression, whereas none of the 55 knees with no scan abnormality at entry progressed. The strong negative predictive power of scintigraphy could not be accounted for by disease severity or any combination of entry variables. Pain severity predicted a subsequent operation, but age, sex, symptom duration, and obesity had no predictive value. CONCLUSIONS--Scintigraphy predicts subsequent loss of joint space in patients with established OA of the knee joint. This is the first description of a powerful predictor of change in this disease. The finding suggests that the activity of the subchondral bone may determine loss of cartilage.